Unconstitutional house caretaking (2021)
The Philippine House of Representatives has, in recent years, circumvented the constitutional provision on the filling of vacancies by choosing to appoint a district "caretaker" upon the death, resignation, expulsion, or incapacity of a district representative. Legislative "caretaking" allows the incumbent Speaker of the House to play patronage politics and handpick, without any qualification and guided only by "tradition," another representative who will then have control over the budget allocations and projects for the district. More than assailing the practice of district caretaking as baseless, this Note argues that the very practice of not filling up vacancies is unconstitutional. The practice goes against the intent of the framers of the Constitution, violates state principle and policy, and constitutes an illegal act in cases when the vacancy arises within the prescriptive period for conducting special elections. Contrary to contemporary interpretation and practice by Congress, it is Republic Act No. 7166, not Republic Act No. 6645, which is the prevailing law governing vacancies. This requires the holding of a special election by the Commission on Elections upon the occurrence of the vacancy and without the need for any prior notification from Congress.
Keywords: Constitutional law; Political patronage